2018
DOI: 10.1038/s41598-018-19808-x
|View full text |Cite
|
Sign up to set email alerts
|

Four-week individual caging of male ICR mice alters body composition without change in body mass

Abstract: Understanding the physiological implications of caging conditions for mice is crucial in improving the replicability and reliability of animal research. Individual caging of mice is known to alter mouse psychology, such as triggering depression-like symptoms in mice, suggesting that caging conditions could have negative effects on mice. Therefore, we hypothesized that individual caging could affect the physical composition of outbred mice. To investigate this, dual X-ray absorptiometry (DXA) was used to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The data from the current study suggests that individual housing of mice at these standard temperatures may lead to even further deviation from human physiology and should therefore be regarded as an additional limitation to the translational value of such mouse research models. Moreover, the results from this and other studies (8, 35) show that the metabolic derangements observed in individually versus socially housed mice are not always reflected in higher body weights. This stresses that potential confounding influences of environment on mouse physiology may remain unnoticed when only body weight is monitored.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The data from the current study suggests that individual housing of mice at these standard temperatures may lead to even further deviation from human physiology and should therefore be regarded as an additional limitation to the translational value of such mouse research models. Moreover, the results from this and other studies (8, 35) show that the metabolic derangements observed in individually versus socially housed mice are not always reflected in higher body weights. This stresses that potential confounding influences of environment on mouse physiology may remain unnoticed when only body weight is monitored.…”
Section: Discussionsupporting
confidence: 50%
“…Basal CORT levels were however not affected during adolescence due to individual housing (but see below). As (home cage) physical activity levels were not monitored in the current study, a potential contribution of that factor to the differences in fat deposition observed between individually and socially housed mice in the current study cannot be excluded, although such an effect may be unlikely (35). It remains unknown whether the increased adiposity in individually housed mice may be of functional relevance to the animal.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Whereas the reduced body weight due to individual housing is transient, the reduced bone length and width persist into adulthood. Bone length in mice typically correlates to growth rate between 3 and 5 weeks of age [41], but as changes in bone mass and bone mineral density have also been reported in mice that were individually housed from adult age onwards [10,42], reduced…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on the results of a systematic review and meta-analysis we recently conducted [8], we concluded that individual versus social housing of rats and mice alters metabolic health status. For instance, individually housed mice show increased energy intake and altered adipose tissue deposition compared to socially housed mice, thought the extent to which this occurs may be sensitive to strain, diet and other environmental factors [9][10][11][12]. Social isolation stress may indeed affect the neurobiological control of food intake by affecting brain area's involved in energy balance regulation such as the hypothalamus [13,14] and the reward system [15].…”
Section: Introductionmentioning
confidence: 99%